2011
DOI: 10.4155/tde.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Insonation Frequency Selection May Assist Detection and Therapeutic Delivery of Targeted Ultrasound Contrast Agents

Abstract: Background: Ultrasound-targeted drug delivery relies on the unique nature of ultrasound contrast agents – they are microbubbles that respond strongly to ultrasound. Intravenously injected microbubbles are smaller than a blood cell. By increasing the ultrasound power, the bubbles can be ruptured at the targeted endothelial wall, locally releasing any molecules in the bubble shell. Furthermore, ultrasound-activated microbubbles are known to cause sonoporation – the process by which ultrasound drives molecules th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Previous studies of such a configuration showed that the linear natural frequency of the bubble near the wall is shifted downward by a factor of √ 2/3 ≈ 0.82 [16,18]. It was found to be numerically consistent with the predicted values, although for bubbles that were somewhat larger than typical contrast-agent bubbles [15]. Recent experiments with high-speed imaging also demonstrated a downshift in the linear response frequency of actual contrast agents on biological target surfaces [19].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Previous studies of such a configuration showed that the linear natural frequency of the bubble near the wall is shifted downward by a factor of √ 2/3 ≈ 0.82 [16,18]. It was found to be numerically consistent with the predicted values, although for bubbles that were somewhat larger than typical contrast-agent bubbles [15]. Recent experiments with high-speed imaging also demonstrated a downshift in the linear response frequency of actual contrast agents on biological target surfaces [19].…”
Section: Introductionsupporting
confidence: 62%
“…[18] and the potential value of a frequency shift in identifying targeted microbubbles via a filtering approach has been recognized in Ref. [15]. Therefore, it is expected that the acoustic signature of initially "silent" small bubbles will become more pronounced as they approach the wall.…”
Section: -4mentioning
confidence: 97%
See 1 more Smart Citation
“…Signals from molecularly targeted adherent agents can be obscured by echoes from tissue and freely circulating microbubbles. Methods have been suggested to distinguish between molecularly targeted and freely floating microbubbles or tissue [125127]. …”
Section: Targeted Drug-delivery Mechanismsmentioning
confidence: 99%
“…This may be significant because the resonant frequency of the microbubbles depends on their size. If strategies for detection of targeted agents are based on shifts in the microbubble frequency when on target (Payne et al, 2011), unexpected results may occur when these strategies are tested in vivo.…”
Section: Discussionmentioning
confidence: 99%